VD_FINDINFO HC / 2012 / 704 vom 12. Oktober 2012 - VD Tribunal cantonal (2012)
APPEL EN CAUSE, EFFETS ACCESSOIRES DU DIVORCE, COMPÉTENCE RATIONE MATERIAE | 64 LDIP, 320 CPC (CH), 322 al. 1 CPC (CH), 81 CPC (CH)